The Escherichia coli Phospholipase PldA Regulates Outer Membrane Homeostasis via Lipid Signaling - May, Kerrie L. (mBio, 2018)
The outer membrane (OM) bilayer of Gram-negative bacteria is biologically unique in its asymmetrical organization of lipids, with an inner leaflet composed of glycerophospholipids (PLs) and a surface-exposed outer leaflet composed of lipopolysaccharide (LPS). This lipid organization is integral to the OM’s barrier properties. Perturbations of the outer leaflet by antimicrobial peptides or defects in LPS biosynthesis or transport to the OM cause a compensatory flipping of PLs to the outer leaflet. As a result, lipid asymmetry is disrupted and OM integrity is compromised. Recently, we identified an Escherichia coli mutant that exhibits aberrant accumulation of surface PLs accompanied by a cellular increase in LPS production. Remarkably, the observed hyperproduction of LPS is PldA dependent. Here we provide evidence that the fatty acids generated by PldA at the OM are transported into the cytoplasm and simultaneously activated by thioesterification to coenzyme A (CoA) by FadD. The acyl-CoAs produced ultimately inhibit LpxC degradation by FtsH. The increased levels of LpxC, the enzyme that catalyzes the first committed step in LPS biosynthesis, increases the amount of LPS produced. Our data suggest that PldA acts as a sensor for lipid asymmetry in the OM. PldA protects the OM barrier by both degrading mislocalized PLs and generating lipid second messengers that enable long-distance signaling that prompts the cell to restore homeostasis at a distant organelle.